WAR CRIMES IN INTERNATIONAL LAW: AN INTRODUCTION - Michael Cottier (terAs Law Review : Jurnal Hukum Humaniter dan HAM, 2005)
Under international humanitarian law (IHL}, war crimes have been developed, particularly at great speed since the early 1990s and there have been many changes as, for example: the criminalization of violations of IHL. In this paper the author will examine, among others, the meaning of war crimes in international law, the concept of war crimes, list and definitions of the war crimes. The development of war crimes tribunal until the establishing of the International Criminal Court (ICC) can be found in this paper as well